Genetic analysis of the functional relationship between colicin E3 and its immunity protein. - Mock, M (1984)
Partial deletions in the immunity gene of the colicin E3 operon were used to study possible functions of the immunity protein besides protection against exogenous colicin. Nuclease BAL-31 was used to create a series of carboxyl-terminal deletions of the immunity gene. Mutants displaying lowered immunity against exogenous colicin were found, and six that had reduced but detectable levels of immunity were chosen for further analysis. DNA sequence analysis of the deletions showed that all six terminated within the last five codons of the immunity gene. The wild-type immunity gene was replaced by each of the six mutated immunity genes in a plasmid containing an otherwise functional colicin E3 operon. Transformants containing the resulting plasmids produced smaller colonies on solid medium and grew more slowly in liquid culture than transformants carrying the wild-type colicin and immunity genes. This result suggested that immunity protein was required to protect the cell against endogenous colicin E3. This idea was confirmed in experiments in which the colicin E3 and immunity genes were independently cloned on two compatible plasmid vectors.